2016
DOI: 10.1021/acs.est.5b04904
|View full text |Cite
|
Sign up to set email alerts
|

Organic Contaminant Abatement in Reclaimed Water by UV/H2O2 and a Combined Process Consisting of O3/H2O2 Followed by UV/H2O2: Prediction of Abatement Efficiency, Energy Consumption, and Byproduct Formation

Abstract: UV/H2O2 processes can be applied to improve the quality of effluents from municipal wastewater treatment plants by attenuating trace organic contaminants (micropollutants). This study presents a kinetic model based on UV photolysis parameters, including UV absorption rate and quantum yield, and hydroxyl radical (·OH) oxidation parameters, including second-order rate constants for ·OH reactions and steady-state ·OH concentrations, that can be used to predict micropollutant abatement in wastewater. The UV/H2O2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 56 publications
1
74
2
Order By: Relevance
“…More extensive transformation and/or removal of bulk organic matter yields significant benefits for advanced treatment with respect to membrane fouling (Stanford, Pisarenko, Holbrook, & Snyder, ), ozone efficacy due to reductions in dissolved organic carbon concentrations (Lee et al., ), and the efficacy of UV disinfection, photolysis, or advanced oxidation due to increases in UV transmittance (Lee et al., ). The current study evaluated changes in fluorescence, as measured by EEMs, peak fluorescence, and regional fluorescence, and also changes in UV absorbance to describe how biological treatment might impact downstream treatment efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More extensive transformation and/or removal of bulk organic matter yields significant benefits for advanced treatment with respect to membrane fouling (Stanford, Pisarenko, Holbrook, & Snyder, ), ozone efficacy due to reductions in dissolved organic carbon concentrations (Lee et al., ), and the efficacy of UV disinfection, photolysis, or advanced oxidation due to increases in UV transmittance (Lee et al., ). The current study evaluated changes in fluorescence, as measured by EEMs, peak fluorescence, and regional fluorescence, and also changes in UV absorbance to describe how biological treatment might impact downstream treatment efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the same reactor assumptions in Lee et al. (), including an electrical efficiency of 30% and a path length of 10 cm, the average UV 254 absorbance of 0.171 cm −1 for the 2‐day SRT results in energy consumption values of 0.030 and 0.372 kWh/m 3 for UV doses of 80 mJ/cm 2 (i.e., disinfection) and 1,000 mJ/cm 2 (i.e., advanced oxidation), respectively. In contrast, the average UV 254 absorbance of 0.135 cm −1 for the 20‐day SRT results in lower energy consumption values of 0.024 and 0.301 kWh/m 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens could be attenuated by optimizing upstream wastewater treatment and/or the disinfection processes at the AWPF (e.g., O 3 , UV, and free chlorine disinfection in the ESB). However, the required O 3 dose would likely exceed an O 3 /TOC ratio of 1.0 (Gerrity et al, ), and this dosing level has been shown to form up to 30 μg/L of bromate in local wastewater (Lee et al, ). Considering that the DPR flow accounted for up to 10%–40% of the overall water supply for the 25% and 100% diversions, respectively, the DPR flow might add 3–12 μg/L of bromate to local drinking water.…”
Section: Resultsmentioning
confidence: 99%
“…This would either exceed the USEPA maximum contaminant level (MCL) of 10 μg/L outright or when combined with the baseline level of bromate formed during ozonation at AMSWTF and RMWTF. Alternatively, bromate formation could be mitigated with the chlorine–ammonia process (Neemann, Hulsey, Rexing, & Wert, ) or by hydrogen peroxide addition (von Gunten, ), but the formation of alternative disinfection products might be a concern, the reduction in bromate might still be inadequate (Lee et al, ), disinfection efficacy might be compromised (Gamage, Gerrity, Pisarenko, Wert, & Snyder, ), and O&M costs would increase (Plumlee et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The energy consumption of the developed electrochemical cotton filter technology for TC treatment is calculated at an applied total cell potential of 2.0 V, by assuming 31 electrons transferred per TC molecule, to be 1.2 kWh/kg COD (The COD used here is the theoretical COD). This value is comparative with state-of-the-art electrochemical oxidation processes with an energy consumption in the range of 5-100 kWh/kg COD [36][37][38][39]. Alternatively, the energy per volume treated is calculated to be only 0.05 kWh/m 3 .…”
Section: Performance Of the Cotton Filter Towards Tc Removalmentioning
confidence: 99%